Comparing the effects of motor control exercises and PNF exercises on postural control, strength, endurance, and proprioception in women with chronic nonspecific low back pain - Fatemeh Karkamandi; Hadi Miri; Amir Letafatkar; Mina Haghighi (Sport Sciences and Health Research)
Background: Low back pain is a common debilitating condition and a major clinical and socio-economic problem in the most industrialized and non-industrialized countries.Aim: The aim of this study was to compare the effect of motor control exercises and PNF exercises on postural control, strength, endurance and proprioception in women with chronic non-specific low back pain.Materials and Methods: Forty-five women with non-specific chronic low back pain selected by convenience sampling and randomly divided into three groups of 15 (motor control exercises, PNF exercises, and control group). The pre-test included posture control, flexor and extensor muscle strength of the trunk, trunk muscle endurance, and proprioception using Y balance, dynamometer, McGill, and Goniometer tests, respectively. The subjects of the experimental groups performed the training program for 8 weeks under the supervision of the instructor and according to the training protocol. Then, the post-test was performed. Paired t-test and analysis of covariance at the significance level of 0.05 were used to collect data.Results: The results showed that motor control and PNF exercises improved proprioception, postural control, endurance, and strength of trunk flexor and extensor muscles in women with non-specific chronic low back pain (α≤0.05). The results also showed that there was no significant difference between the effects of motor control and PNF exercises on proprioception, postural control, flexor muscle endurance, and extensor muscle strength (α≥0.05).Discussion: Motor control and PNF exercises are effective in improving the proprioception, postural control, endurance, and strength of flexor and extensor muscles of the trunk with non-specific chronic low back pain, and both training methods are effective in treating chronic non-specific low back pain.